FALSE CAMPAIGN DALAM IKLAN LAYANAN MASYARAKAT PASKA KENAIKAN HARGA BAHAN BAKAR MINYAK 1 OKTOBER 2005 - Dektisa Hagijanto, Andrian (Nirmana, 2006)
Due to publicÂ’s reaction initiated by the raised oil prices per October 1%2C 2006%2C the government launched several Public Service Advertisements featuring a religious figure%2C an education figure%2C and a former cabinet member. These advertisements%2C however%2C raised some critiques. Public Service Advertisement (PSA) is a social discourse that can influence the public. In essence%2C PSA is objective and in general portray the reality in our community. Blunder in creating PSAÂ’s will cause social reaction%2C false campaign%2C and even empty discourse that will actually make blunder for the advertisers. Abstract in Bahasa Indonesia : Akibat reaksi masyarakat yang dipicu oleh kenaikan harga bahan bakar minyak per 1 Oktober 2006 maka pemerintah meluncurkan iklan layanan masyarakat yang memakai figur tokoh agama%2C pendidikan%2C dan mantan menteri. Namun iklan layanan masyarakat ini juga menuai kritik. Iklan Layanan Masyarakat (ILM) adalah diskursus sosial yang dapat mempengaruhi khalayak masyarakat. Sejatinya ILM adalah objektif dan menggambarkan realitas masyarakat pada umumnya. Kecerobohan di dalam membuat ILM akan memancing reaksi sosial%2C kampanye salah (false campaign)%2C dan bahkan empty discourse yang justru akan menjadi blunder bagi pengiklan. Public Service Advertisement post oil price increase of 1 October 2006%2C false campaign%2C subjective interpretation%2C communication using symbol as the signified.